A 20-yr longitudinal study of Olympic oarsmen - Hagerman, F. C.; Fielding, R. A.; Fiatarone, M. A.; Gault, J. A.; Kirkendall, D. T.; Ragg, K. E.; Evans, W. J. (Medicine & Science in Sports & Exercise, 1996)
Nine 1972 silver-medalist oarsmen were studied before the Olympic Games and 10 and 20 yr later. Peak power, metabolic responses, and heart rate were recorded during rowing ergometry; blood lactate was measured following exercise. The skinfold equation yielded percent body fat. The average change (multiple analysis of variance) among measurements from 1972 to 1992 was 37.5 +/- 3% (P < 0.01). Average changes between 1972 and 1982 and between 1982 and 1992 were similar, 17 and 18%, respectively (P < 0.01). The most significant change between 1972 and 1992 was decreased peak blood lactate (106%). Decreases in peak power, VE, and VO2 (ml.kg-1.min-1) were all similar, approximately 40%, and were significant. Body fat increased (from 12.3 to 15.6%), and absolute VO2 and relative VO2 (lean body mass) decreased 30% (P < 0.01). Only body weight, heart rate, and O2 pulse showed smaller changes, but these changes were still significant (P < 0.05). Relative peak VO2 decreased from 65.5 to 46.8 ml.kg-1.min-1 from 1972 to 1992 and at a rate of 10%.decade-1. The most significant changes between 1972 and 1982 were increases in percent body fat (from 12.3 to 16.3%) and decreases in VO2 values (P < 0.01). There was less change in body fat between 1982 and 1992, but lactate significantly decreased (P < 0.01), as did peak power and absolute and relative VO2 and VE. Although fitness levels in former elite oarsmen decreased each decade, these declines were somewhat arrested by regular aerobic training. Body fat increased and metabolic capacity decreased rapidly during the first decade, whereas anaerobic capacity decreased more significantly in the second decade. Anaerobic capacity diminished at a significantly greater rate than aerobic capacity, probably as a result of the aging process and emphasis on aerobic training in post-competitive years.